Integrated conjugative plasmid drives high frequency chromosomal gene transfer in Sulfolobus islandicus - Sanchez-Nieves, Ruben L.; Zhang, Changyi; Whitaker, Rachel J. (Frontiers in Microbiology, 2023)
Gene transfer in crenarchaea has been observed within natural and experimental populations of Sulfolobus. However, the molecular factors that govern how gene transfer and recombination manifest themselves in these populations is still unknown. In this study, we examine a plasmid-mediated mechanism of gene transfer in S. islandicus that results in localized high frequency recombination within the chromosome. Through chromosomal marker exchange assays with defined donors and recipients, we find that while bidirectional exchange occurs among all cells, those possessing the integrated conjugative plasmid, pM164, mobilize a nearby locus at a significantly higher frequency when compared to a more distal marker. We establish that traG is essential for this phenotype and that high frequency recombination can be replicated in transconjugants after plasmid transfer. Mapping recombinants through genomic analysis, we establish the distribution of recombinant tracts with decreasing frequency at increasing distance from pM164. We suggest the bias in transfer is a result of an Hfr (high frequency recombination)-like conjugation mechanism in this strain. In addition, we find recombinants containing distal non-selected recombination events, potentially mediated by a different host-encoded marker exchange (ME) mechanism.